Hubungan Kebiasaan Olahraga Dengan Kejadian Dismenorhoe Pada Remaja Putri Kelas 2 di SMAN 2 Bangkalan - Aim Matun Nadhiroh (Jurnal Keperawatan Muhammadiyah, 2022)
Dysmenorrhea is pain during menstruation that can be felt in the lower abdomen or waist. Dysmenorrhea can interfere with daily activities and can have an impact on decreasing work productivity. Dysmenorrhea can be treated pharmacologically and non-pharmacologically, for example, yoga and various distractions. The purpose of this study was to determine the incidence of dysmenorrhea in adolescent girls in grade 2 of SMAN 2 Bangkalan.The method in this study uses an analytical survey with a case control design. The population is all 2nd grade teenage girls as many as 120 teenagers. The sample is 60 adolescents with dysmenorrhea and 30 adolescents without dysmenorrhea at random with Simple Random Sampling. The instrument used is a questionnaire, data analysis using the Chi sguare Correlation and Odd Ratio (OR) test.The results of the study showed that the majority of young women who were not active in sports were 78.9%. Teenage girls who experience dysmenorrhea as much as 66.7%. Adolescent girls who are not active in sports and experience dysmenorrhea 78.9%. Teenage girls who are active and do not experience dysmenorrhea as much as 79%. The results of statistical tests showed that there was a relationship between exercise habits and the incidence of dysmenorrhea in grade 2 adolescent girls at SMAN 2 Bangkalan with p<α (0.000 <0.05) and the Odd Ratio (OR) test showed that female adolescents who were not active in sports were 14,000 times more likely to be physically active. at risk for dysmenorrhea.Information about dysmenorrhea should be given early to increase knowledge in dealing with dysmenorrhea properly and correctly. And exercise can be used as an alternative intervention for dysmenorrhea.